Castor bean isocitrate lyase lacking the putative peroxisomal targeting signal 1 ARM is imported into plant peroxisomes both in vitro and in vivo. - Gao, X (1996)
To understand and manipulate plant peroxisomal protein targeting, it is important to establish the universality or otherwise of targeting signals. Contradictory results have been published concerning the nature and location of the glyoxysomal/peroxisomal targeting signal of isocitrate lyase (ICL). L.J. Olsen, W.F. Ettinger, B. Damsz, K. Matsudaira, A. Webb, and J.J. Harada ([1993] Plant Cell 5: 941-952) concluded that the last 5 amino acids (AKSRM) of Brassica napus ICL were sufficient and the last 37 amino acids were necessary for targeting to Arabidopsis leaf peroxisomes. In contrast, R. Behari and A. Baker ([1993]) J Biol Chem 268: 7315-7322) could find no requirement for the almost identical carboxy-terminal sequence AKARM for import of Ricinus communis ICL into isolated sunflower cotyledon glyoxysomes. To resolve this discrepancy, the import characteristics of a mutant R. communis ICL lacking the last 19 amino acids of the carboxy terminus was studied. ICL delta 19 was able to be imported by isolated sunflower glyoxysomes and by tobacco leaf peroxisomes when expressed transgenically. These results demonstrate that the in vitro import system faithfully reflects targeting in vivo, and that the source of the organelles (Arabidopsis versus sunflower, leaf peroxisomes versus seed glyoxysomes) is not responsible for observed differences between B. napus and R. communis ICL. The R. communis enzyme would therefore appear to possess an additional glyoxysome/peroxisome targeting signal that is lacking in the B. napus protein.